The Role of Threshold of Free Shipping Promotion and Product Type on Impulsive Buying Behaviour in E-Commerce Platform - Readdy Aria Yendola; Nila Armelia Windasari (The Winners, 2022)
The research proposed a new insight on how the threshold of free shipping (TFS) promotion type and product type could affect consumers to buy impulsively through emotional consumer reaction of hedonic motivation and positive affect, using the S-O-R model. The data were analyzed based on 188 responses who had completed questionnaires. Data were collected using the purposive sampling method with a minimum sample size of 138 from GPower calculation. The research used ANOVA and Regression Analysis to assess the model and utilizes SPSS. The result clearly illustrates that the maximum threshold of free shipping type with the hedonic product would lead more to consumer hedonic motivation. At the same time, the minimum threshold of free shipping type will induce too when combined with utilitarian products. Furthermore, consumer feelings of hedonic motivation and positive affect play an essential role in determining consumers’ impulsive buying behavior. The research benefits stakeholders in using and maximizing the free shipping promotion program.